Mexico Country Program Evaluation : An Evaluation of the World Bank Group’s Support to Mexico (2008–17) - Independent Evaluation Group (World Bank, Washington, DC, 2018)
This evaluation assesses the development effectiveness of the Bank Group’s country program in Mexico between 2008 and 2017 to inform the next CPF (FY19). The country program evaluation (CPE) will deepen knowledge on what has and has not worked and provide timely feedback on upcoming operational choices. The report will inform not only the Bank Group’s Mexico Country Management Unit and Mexican government but also a wider Bank Group audience, focused on middle-income countries (MICs) and other development practitioners. The evaluation examines the relevance and effectiveness of the Bank Group program in Mexico in its core areas, and also, as a methodological innovation, examines four overarching areas: (i) the extent to which the Bank Group contributed to identifying Mexico’s binding development constraints and to promoting sound policy choices; (ii) Bank Group contributions to Mexico’s results in reducing poverty and promoting shared prosperity; (iii) the effectiveness of Bank Group use of lending, knowledge, and convening power services in shaping its role; and (iv) the extent to which Bank Group support to Mexico’s development innovations was beneficial to the Bank Group’s knowledge base and to other Bank Group member countries. Overall results reflect both program results in core areas and the answers to the overarching questions. The overview of this report is also available in Spanish.